Emotional Spiritual Quotient (ESQ) dalam Pembelajaran Pendidikan Agama Islam Kurikulum 2013 - Sulaiman, Moh; Al Hamdani, M. Djaswidi; Aziz, Abdul (Jurnal Penelitian Pendidikan Islam, 2018)
This article finds out that the Emotional Spiritual Quotient (ESQ) aspects in the Curriculum 2013 of the Islamic Education Learning includes faith and piety, noble character, honesty, discipline, responsibility, caring (mutual cooperation, tolerance, peace), polite, responsive and pro-active confidence in interacting with family, friends, teachers, the environment and society. However, among some aspects of ESQ that are very significant influence in learning and assessment is an honest attitude. Honesty becomes the determinant of the integrity of education as well as the guarantor of the quality of education. Emotional intelligence also teaches about the integrity of honesty of commitment, vision, creativity, mental resilience of wisdom and mastery. EQ is an intelligence that gives awareness of one's own and others' feelings, giving a sense of empathy, love, motivation and the ability to respond to grief and happiness.